Potassium tert-butoxide mediated C–C, C–N, C–O and C–S bond forming reactions. Issue 41 (6th October 2020) - Madasu, Jayashree; Shinde, Shital; Das, Rudradip; Patel, Sagarkumar; Shard, Amit
Abstract : Potassium tertiary butoxide (KO t Bu) mediated constructions of C–C, C–O, C–N, and C–S bonds are reviewed with special emphasis on their synthetic applications. Abstract : Potassium tertiary butoxide (KO t Bu) mediated constructions of C–C, C–O, C–N, and C–S bonds are reviewed with special emphasis on their synthetic applications. KO t Bu can be used to perform reactions already known to be carried out using transition metals, but it has advantages in terms of environmental congruence and economic cost. KO t Bu is widely employed in organic synthesis to mediate the construction of C–C, C–O, C–N, C–S and miscellaneous bonds in good to excellent yields. Synthetic uses of KO t Bu in coupling, alkylation, arylation, α-phenylation, cyclization, Heck-type, annulation, photo-arylation, aromatic-substitution, amidation, and silylation reactions are summarized and discussed. The mechanisms through which KO t Bu carries out a specific reaction are also discussed. One of the goals of this review is to attract the attention of chemists as to the benefits of using KO t Bu as an environmentally benign alternative to transition metals and its applications in the construction of chemical bonds with predominant importance in organic synthesis. This review completely covers the synthetic protocols that have been performed using KO t Bu in the last two decades.